2009
DOI: 10.1002/smll.200801476
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotube Surfaces: 15 nm—An Optimal Length Scale of Surface Topography for Cell Adhesion and Differentiation

Abstract: Studies of biomimetic surfaces in medicine and biomaterial fields have explored extensively how the micrometer-scale topography of a surface controls cell behavior, but only recently has the nanoscale environment received attention as a critical factor for cell behavior. Several investigations of cell interactions have been performed using surface protrusion topographies at the nanoscale; such topographies are typically based on polymer demixing, ordered gold cluster arrays, or islands of adhesive ligands at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

27
446
2
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 503 publications
(481 citation statements)
references
References 30 publications
27
446
2
6
Order By: Relevance
“…These findings are contrary to our results with human mesenchymal stem cells on a range of nanotubes with 30-to 100-nm diameter, where cell stretching and expression of osteogenic differentiation markers was highest on 100 nm nanotubes (4). Park et al (2,3) illustrated that the optimum length scale for cell vitality and differentiation was shown to be the small-diameter nanotubes (Ϸ15 nm), in contrast to the large diameter of 100nm in our study (4). The opposite results found in the refs.…”
contrasting
confidence: 82%
See 1 more Smart Citation
“…These findings are contrary to our results with human mesenchymal stem cells on a range of nanotubes with 30-to 100-nm diameter, where cell stretching and expression of osteogenic differentiation markers was highest on 100 nm nanotubes (4). Park et al (2,3) illustrated that the optimum length scale for cell vitality and differentiation was shown to be the small-diameter nanotubes (Ϸ15 nm), in contrast to the large diameter of 100nm in our study (4). The opposite results found in the refs.…”
contrasting
confidence: 82%
“…In their Letter to the Editor, von der Mark et al (1) stated that they found adhesion, proliferation, migration, and osteogenic differentiation of rat bone marrow mesenchymal stem cells (MSCs) to be highest on 15-nm TiO 2 nanotubes and to be dramatically decreased on 70-and 100-nm nanotubes (2,3). These findings are contrary to our results with human mesenchymal stem cells on a range of nanotubes with 30-to 100-nm diameter, where cell stretching and expression of osteogenic differentiation markers was highest on 100 nm nanotubes (4).…”
mentioning
confidence: 99%
“…Culturing human mesenchymal stem cells (MSCs) on a range of nanotubes with diameters between 30 and 100 nm, cell stretching and expression of osteogenic differentiation markers was highest on 100-nm nanotubes, whereas cell-adhesion rates increased with decreasing tube diameter, with a maximum at 30 nm. This finding is particularly striking in light of previous contrary reports showing that nanoscale-dependent differentiation of MSCs to osteoblasts followed in the opposite direction (2,3). In these studies, data were presented showing that not only adhesion, proliferation, and migration, but also osteogenic differentiation of rat bone marrow MSCs were highest on 15-nm nanotubes and decreased dramatically on 70-and 100-nm nanotubes.…”
mentioning
confidence: 69%
“…In order to improve the surface functionality of the titanium and its alloy, various methods, such as sand blasting, electrochemical anodization and plasma spraying, were carried out to build bioactive structures on their surface [9,10]. However, the above methods are not suitable for porous titanium scaffolds surface modification because these methods are difficult to homogeneously modify the complex micro-structured scaffolds.…”
Section: Introductionmentioning
confidence: 99%